Body composition assessment in patients with spinal cord injury by bioimpedance - Mariana Buratti Mascarenhas; Nicolli S Scarabelli; Cinthia Bittar; Felipe R Mascarenhas; Orcizo F Silvestre; Alberto Cliquet (International Journal of Spine Research - Peertechz Publications, 2022)
Background: Individuals with spinal cord injury develop alterations in the metabolism of carbohydrates and lipids, chronic inflammation, abnormal control of glycemia, as well as loss of lean mass, and increased adiposity, these being some risk factors for the development of diseases and decreased quality of life. This research aimed to investigate the body composition during a treatment protocol with NMES in a spinal cord injured population.  Methods: An initial bioimpedance evaluation using Biodynamics 310e was performed on 19 spinal cord injury patients. During the following 4 months, they received neuromuscular stimulation. The individuals ended the clinic once a week and performed NMES for 45 min, 20 min on quadriceps, and 15 min on peroneal nerve, on both legs with a frequency in the range of 18 to 25 Hz. A new bioimpedance test was performed after this period.  Results: For data analysis, a 5% significance level was considered. There were statistically significant gains in lean mass with p= 0.0001 and a decrease in bio-strength with p= 0.0457. There was a loss of body fat, but not significant.  Conclusion: Individuals with spinal cord injury showed measurable body composition changes during a four-month neuromuscular electrical stimulation treatment.